Protein adsorption on amino acid conjugated self assembled molecules - Eren, Sezin. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2015., 2015)
In this thesis, novel amino acid (conjugated histidine, leucine, serine, tryptophan) conjugated self-assembled molecules (SAMs) were synthesized and used to modify model metallic [Gold, (Au)] and inorganic [Silicon Oxide, (SiO2)] surfaces to investigate protein adsorption. In the first step, Au and SiO2 surfaces were cleaned and modification of surfaces were carried out with 3-mercaptopropanoyl and 3 - (trimethoxysilyl) propane functional groups conjugated amino acids (for Au; histidine, leucine, serine, tryptophan, for SiO2; histidine and leucine), respectively. Syntheses of amino acid conjugated SAMs were characterized with 1H-Nuclear Magnetic Resonance (1H-NMR) Spectroscopy. Au and SiO2 surfaces modified with amino acid conjugated SAMs were characterized water contact angle measurements. We aimed to manipulate and change the adsorption of the proteins (Albumin, Fibrinogen and Immunoglobulin G) on these surfaces using amino acid conjugated SAMs. Protein adsorption was investigated insitu by using Quartz Crystal Microbalance (QCM) biosensors. According to results, target proteins have shown different affinity to the amino acid conjugated Au and SiO2 coated crystals depending the type of the amino acids and concentration. For instance, according to comparison of Histidine modified SiO2 and Au surfaces, properties of surfaces have shown a clear difference and effect on protein adsorption. In addition, according to comparison of Leucine modified SiO2 and Au surfaces, properties of surfaces have shown a clear effect on protein adsorption as having the same surface chemistry. Consequently, it has been observed that these controlled chemistry on the surfaces of materials have a great potential to manipulate protein adsorption for biomedical applications.|Keywords : Self-Assembled Monolayers, Amino acids, Surface Modification, Protein Adsorption, Quartz Crystal Microbalance (QCM) Biosensors.
Keywords: Amino acids.; Biosensors.